Séparations rapides de traces métalliques sur goutte de mercure - E. Mérat; W. Haerdi (CHIMIA)
Fast separations of traces of metals on a mercury drop. The proposed method is based on the adsorption of uncharged complexes of the metals to be separated on the mercury drop. We have demonstrated how the calculation of the various possible complexes allows the determination of the selectivity of the separation. Some examples are given regarding the metal ions Co++, Cu++, Fe+++, Mn++, Pb++ and the ligands OH- and I-.